1978
DOI: 10.1152/jn.1978.41.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular staining reveals different levels of stratification for on- and off-center ganglion cells in cat retina

Abstract: 1. Ganglion cells in the retina of the cat were stained by intracellular dye injection after recording their responses to photic stimulation. 2. All cells encountered were divided into those giving on-responses and those producing off-responses, and the level of dendritic branching of these two groups was compared. Cells giving off-responses were found to branch high in the inner plexiform layer (IPL), near the amacrine cell bodies (sublamina a); those giving on-responses were found to branch lower in the inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
281
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 606 publications
(299 citation statements)
references
References 0 publications
14
281
0
4
Order By: Relevance
“…DeBruyn and Casagrande (1983) found that, on the one hand, the ganglion cells projecting to the dLGN layers containing ON-center cells have dendrites which appear to ramify close to the cell body in the upper part of the inner plexiform layer (IPL); and on the other hand, ganglion cells which project to the dLGN layers containing OFF-center cells have dendrites which appear to extend further from the cell body into the lower part of the IPL. Thus, in the tree shrew, as in other species (Famiglietti and Kolb, 1976;Nelson et al, 1978) the spatial segregation of ON-and OFF-center cells appears to be organized initially in the retina. Therefore, we explain the fact that during the dark period exist c-Fos expression in the GCL and the INL because there are phasic and tonic OFFcenter cells active, which after a dark period (in this study 15 h), the phasic cells are inhibited, but not the tonic ones.…”
Section: Ganglion Cell Layer and Inner Nuclear Layermentioning
confidence: 90%
“…DeBruyn and Casagrande (1983) found that, on the one hand, the ganglion cells projecting to the dLGN layers containing ON-center cells have dendrites which appear to ramify close to the cell body in the upper part of the inner plexiform layer (IPL); and on the other hand, ganglion cells which project to the dLGN layers containing OFF-center cells have dendrites which appear to extend further from the cell body into the lower part of the IPL. Thus, in the tree shrew, as in other species (Famiglietti and Kolb, 1976;Nelson et al, 1978) the spatial segregation of ON-and OFF-center cells appears to be organized initially in the retina. Therefore, we explain the fact that during the dark period exist c-Fos expression in the GCL and the INL because there are phasic and tonic OFFcenter cells active, which after a dark period (in this study 15 h), the phasic cells are inhibited, but not the tonic ones.…”
Section: Ganglion Cell Layer and Inner Nuclear Layermentioning
confidence: 90%
“…The position and extent of labeled dendrites was then referenced with respect to these retinal landmarks. The I PL was divided into On and Off sublaminas using commonly accepted standards in which the inner three-fifths is considered On and the outer two-fifths Off (Famiglietti and Kolb, 1976;Nelson et al, 1978;Wong and Oakley, 1996). Both methods gave equivalent results and, because the former was less labor intensive, it was used more frequently.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the axons of On-cone and Off-cone bipolar cells terminate in two distinct strata of the inner plexiform layer (IPL) in which they form synapses with the dendrites of On and Off retinal ganglion cells (Famiglietti and Kolb, 1976;Nelson et al, 1978). In contrast, early in development, the dendritic processes of ganglion cells ramify throughout the IPL (Dann et al, 1988;Maslim and Stone, 1988;Ramoa et al, 1988).…”
mentioning
confidence: 99%
“…Because the upsilon cells are OFF-type cells with no evidence for ON-OFF responses (i.e., no significant responses to both light intensity increments and decrements) (Fig. 3e), we expect that they would correspond to a cell whose dendrites narrowly stratify in the outer part of the inner plexiform layer (Nelson et al, 1978;Peichl and Wassle, 1981). Also, because the upsilon cells do not show any significant S-cone/(L ϩ M)-cone opponent response properties, we do not expect them to correspond to the sparse or giant sparse (melanopsinexpressing) cells (Dacey and Packer, 2003;Dacey, 2004;Dacey et al, 2005).…”
Section: Possible Morphological Correlate Of the Upsilon Cellsmentioning
confidence: 99%